2007
DOI: 10.1080/10428190701559124
|View full text |Cite
|
Sign up to set email alerts
|

T-cell/histiocyte-rich B-cell lymphoma: Clinical presentation, management and prognostic factors: report on 61 patients and review of literature

Abstract: T-cell/histiocyte-rich B-cell lymphoma (TC/HRBCL) is a rare subtype of diffuse large B-cell non-Hodgkin's lymphoma (DLBCL) with characteristic morphologic and immunophenotypic features, often misdiagnosed as Hodgkin's lymphoma and peripheral T-cell lymphoma. Few and conflicting clinical data are available in the literature addressing optimal treatment, prognosis and outcome. We retrospectively reviewed all patients diagnosed and managed at our institution between 1995 and 2004 diagnosed with T-cell-rich-B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 30 publications
2
53
2
Order By: Relevance
“…[58][59][60] It is a rare large B-cell lymphoma. It is most commonly seen in middle-aged men, and is associated with an aggressive clinical course.…”
Section: Dlbcl Subtypes T-cell/histiocyte-rich Large B-cell Lymphomamentioning
confidence: 99%
“…[58][59][60] It is a rare large B-cell lymphoma. It is most commonly seen in middle-aged men, and is associated with an aggressive clinical course.…”
Section: Dlbcl Subtypes T-cell/histiocyte-rich Large B-cell Lymphomamentioning
confidence: 99%
“…Although most studies included a relatively small number of patients and were of a retrospective nature, similar outcomes of THRLBCL to that of DLBCL were demonstrated [1,9,10,11,15]. In particular, two case-control studies, which demonstrated no significant difference in OS between THRLBCL and DLBCL, showed CR rates of 52-63% and 3- or 5-year OS of 58-64% for THRLBCL [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of THRLBCL is somewhat different from that of DLBCL-NOS. Thus, it predominantly affects middle-aged males and presents with advanced Ann Arbor stage involving the liver, spleen and bone marrow more frequently than DLBCL-NOS [1,8,9,10,11,12]. However, it is still not clear whether THRLBCL shows a different treatment outcome compared to DLBCL-NOS owing to its pathologic obscurity and extremely rare incidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an indication that dihydroartemisinin interacted with cell surface receptors on the parasite membrane. A number of studies have connected the development of organ toxicity (Tripathi et al, 2010) and cancer to certain receptors (Sato et al, 2005;Seggewiss et al, 2008;Weshi et al, 2007;Mustjoki et al, 2007;Filipovich et al, 1994;Suzuki et al, 2005;Galustian et al, 2009;Farag et al, 2002;Morre et al, 2008). These receptors involved in organ toxicity; in cancer or in other body disorders/diseases are cell surface receptors (UtohNedosa and .…”
Section: Discussionmentioning
confidence: 99%